Mitigating misfortune - Wolkey, Samuel (Kansas State University, 2023)
As flooding continues to be a major issue in cities across the United States, there is an increasing need to manage stormwater on private property rather than allowing the water to run off into sewer systems. This project explores why homeowners should retrofit their single-family residential property to manage stormwater to meet this increased need. To do this, the best vegetated and unvegetated residentially-scaled features are selected based on upfront cost, maintenance hours per year, and potential for captured stormwater volume to score the overall effectiveness of each feature. Selected stormwater features are proposed to capture runoff on the Kansas State University’s President’s Residence site during a storm event. These findings were then used to estimate the runoff on large lot (1.25-5 acres) properties in the Sharingbrook Neighborhood in Manhattan, Kansas, to model how much stormwater could be captured rather than drain into Little Kitten Creek and, eventually, Wildcat Creek. The project also identifies three cities with exemplary residential stormwater management incentive programs: Minneapolis, Minnesota, Portland, Oregon, and Washington D.C. The chosen properties in the Sharingbrook Neighborhood were evaluated based on the projective design to show how the design could benefit Manhattan, Kansas assuming it adopted the strongest incentive program.
Mitigating misfortune: residential stormwater management
Keywords: Residential; Stormwater management; Stormwater management features; Stormwater management incentive programs